Use of traditional medicine and control of hypertension in 12 African countries. Issue 6 (2nd June 2022) - Lassale, Camille; Gaye, Bamba; Diop, Ibrahima Bara; Mipinda, Jean Bruno; Kramoh, Kouadio Euloge; Kouam Kouam, Charles; Ikama, Méo Stéphane; Takombe, Jean Laurent; Damorou, Jean Marie; Toure, Ibrahim Ali; Balde, Dadhi M; Dzudie, Anastase; et al.
Abstract : Background: Use of traditional medicine (TM) is widespread in sub-Saharan Africa as a treatment option for a wide range of disease. We aimed to describe main characteristics of TM users and estimate the association of TM use with control of hypertension. Methods: We used data on 2128 hypertensive patients of a cross-sectional study (convenience sampling), who attended cardiology departments of 12 sub-Saharan African countries (Benin, Cameroon, Congo, Democratic Republic of the Congo, Gabon, Guinea, Côte d'Ivoire, Mauritania, Mozambique, Niger, Senegal, Togo). To model association of TM use with odds of uncontrolled, severe and complicated hypertension, we used multivariable mixed logistic regressions, and to model the association with blood pressure (systolic (SBP) and diastolic (DBP)) we used mixed linear models. All models were adjusted for age, sex, wealth, adherence to hypertension conventional treatment and country (random effect). Results: A total of 512 (24%) participants reported using TM, varying across countries from 10% in the Congo to 48% in Guinea. TM users were more likely to be men, living in rural area, poorly adhere to prescribed medication (frequently due to its cost). Use of TM was associated with a 3.87 (95% CI 1.52 to 6.22)/1.75 (0.34 to 3.16) mm Hg higher SBP/DBP compared with no use; and with greater odds of severe hypertension (OR=1.34; 95% CI 1.04 to 1.74) and of any hypertension complication (OR=1.27; 95% CI 1.01 to 1.60), mainly driven by renal complication (OR=1.57; 95% CI 1.07 to 2.29) after adjustment for measured confounders. Conclusions: The use of TM was associated with higher blood pressure, more severe hypertension and more complications in Sub-Saharan African countries. The widespread use of TM needs to be acknowledged and worked out to integrate TM safely within the conventional healthcare.